Peran Guru Bimbingan Konseling di SMAN 14 Makassar dalam Membangun Karakter Peserta Didik - Gabriel Sipa; Ilham Samudra Sanur; Bustan Bustan (STKIP AL HIKMAH SURABAYA, 2025)
This study examines the role of Guidance and Counseling (BK) teachers in building Students' character at SMAN 14 Makassar. The issues addressed include the lack of internalization of character values such as honesty, responsibility, and discipline, as well as low student participation in counseling activities. The research aims to explore the roles and strategies of BK teachers in supporting students' character development. A qualitative descriptive approach is used to naturally depict phenomena through interviews, observations, and document analysis. The findings indicate that BK teachers play a strategic role through mentoring programs, soft skills training, and discussion groups, which positively impact students' discipline, honesty, and responsibility. However, challenges such as low student participation and limited parental support remain prevalent. This study recommends empowering collaboration with parents and the community, as well as enhancing student engagement in counseling programs.